El Excentrico, 1973-10-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
October 5, 1973 [5 de octubre de 1973]. No volume or issue number. Cover has a photograph of Señorita Mexico, Theresa Anaya, wearing a crown and a cape. She is holding scepter and a bouquet of roses.